Hubungan Penilaian Kinerja Terhadap Hasil Belajar Biologi Materi Sistem Sirkulasi Pada Manusia Di Kelas Xi Madrasah Aliyah Negeri Wara Ambon - M FAQIH SEKNUN; JANABA RENGGIWUR; NURLAILA SOPAMENA (INSTITUT AGAMA ISLAM NEGERI AMBON, 2019)
Learning as an educational process require tactic, approach, method, and various techniques so students can master the material well and deep in the process of teaching and learning, the assessment of the process of teaching and learning outcomes is often ignored, less of attention compared with assessment of learning outcomes. Whereas to find out the learning process was successful or not. Active students or not must be assessed at the time learning is on. Problem in this research is whether the relationship of performance appraisal to learning outcomes and how much the relationship of performance appraisal to learning biology the material circulation system in humans at XI MA Negeri Wara Ambon. This research uses type correlational aim to measure how far the relationship of performance appraisal to learning biology the material circulation system in humans. Result of research show that the relationship of performance appraisal to learning biology the material circulation. The result interpretation value r = 0,67 consist of medium category or enough. Based on the coefficient if determination, so amount of contribution students learning habit is 70.73 %. Therefore, another factor as concept ability, ability of understanding material and question ability determine learning success around 29,27 %. Key Words: Biology, Performance Assessment, Circulation